Post-colonial Literary Texts as Reading Texts within Today’s Schools - Van Kempen, Michiel (Werkwinkel, 2018)
In the making of an edition of the first modern Dutch slavery novel, De stille plantage (1931) by Surinamese author Albert Helman, all kinds of questions arise. There are issues of postcolonial contextualization, historical commentary and the way a text gets its actual significance in high schools. All these issues have their own sensibility in the light of recent fierce debates on slavery and its impact on western societies. The editors do have to take into account more than ever before their own position and questions of ideological responsibility, apart from issues of didactical and pedagogical nature. The question is raised whether such a modern edition does not touch more upon ideological language critique than postcolonial contextualization.